KELEBIHAN DAN KEKURANGAN SERTA KE EMPAT METODE TAFSIR (AL-IJMALI, AT-TAHLILI, AL MUQARAN, AL MAUDHU’I) - Wigati, Ayu; Derry Pramuja, Muhammad (Jurnal Multidisipliner Kapalamada, 2024)
This article discusses the advantages and disadvantages of the four main methods in the science of Al-Qur'an exegesis: al-ijmali, at-tahlili, al-muq?ran, and al-maudhu'i. Each of these methods offers a unique approach to understanding the meaning and messages contained in the Koran, with their respective advantages and disadvantages. The al-ijmali method presents a concise interpretation, making it easier for readers to gain a basic understanding without being too detailed, but lacking in depth. The at-tahlili method explains each verse analytically and in detail, suitable for in-depth understanding, but requires more time. Al-muq?ran's method of comparing various scholarly opinions provides rich insight, but can be confusing for novice readers. Meanwhile, the al-maudhu'i method highlights certain themes in the Al-Qur'an, helps comprehensive thematic understanding, but does not provide the context of the entire verse. This article aims to provide guidance for readers in choosing the exegetical method that best suits their needs to achieve optimal understanding of the Qur'an.